"This Is a Pit of Fire": Associations of Play Materials With Children's Creativity During Play and Internal State Language. Issue 1 (1st January 2022) - Howe, Nina; Tavassoli, Nasim; Leach, Jamie; Farhat, Fadwa; Dehart, Ganie
ABSTRACT: This study investigated how specific characteristics of multipiece, miniature, realistic play props (thematically open-ended village set versus thematically closed-ended train set) designed to enhance children's pretense influenced their scenario creativity, object transformations, and the frequency and use of specific internal-state language. The sample consisted of 7-year-olds ( n = 52) focal children playing with a sibling and a friend and focused on associations of play scenarios (i.e., set-up/organization, expected scenarios, creative scenarios), object use (i.e., set-up/organization, expected use, creative use, and no object), and internal-state language (i.e., references to cognitions, goals, emotions, preferences). Children engaged in more expected scenarios and object use with the closed-ended train set than with the open-ended village set. Play set differentially impacted the use of internal-state language: More references to goals were evident during train play, whereas a trend indicated that children employed more references to cognitions with the village. The pattern of findings indicates that children's play communications may be associated with specific types of play props; thus, different play props may enhance pretense in different ways.